CLIL and the Development of Emotional Competence - Esther Nieto Moreno de Diezmas (Miscelánea: A Journal of English and American Studies, 2013)
The broad spread of CLIL (Content and Language Integrated Learning) bilingual programs is being accompanied by a parallel development of research on the benefits of this platform. Initially, the research interest lay in the study of foreign language acquisition and the acquisition of content of non-language subjects taught in a foreign language. However, in recent times, new areas of the CLIL program’s potential are being discovered. A wide range of studies prove that CLIL implies new benefits: cognitive, social, economic, etc. The goal of this article is to demonstrate that CLIL programs contribute to the development of emotional competence by means of a study conducted with secondary school students of secondary education enrolled in a CLIL program in the Autonomous Community of Castilla La Mancha.